The INFLUENCE OF CITY IMAGE, CITY BRANDING, AND eWOM ON TOURIST VISITING DECISIONS TO DENPASAR CITY - Paramananda, Nyoman (International research journal of management, IT and social sciences, 2022)
Several areas in Bali have developed into tourist areas, one of which is Denpasar City. The number of tourists is one indicator of the success of the tourism industry, but there has been a decrease in the number of tourists visiting Denpasar City since 2016. Finding and determining factors that support tourist decisions in determining tourist destinations is important in the context of developing a tourism marketing strategy. Strategies that can assist the preparation of tourism marketing in order to influence the decision of tourists to visit include the formation of city image, city branding, and eWom. This study aims to analyze the effect of city image, city branding, and eWom on the decision to visit tourists to Denpasar City. Collecting data using a questionnaire distributed directly to the respondents. The population in this study are tourists who visit Denpasar City. In this study using 95 respondents respondents. The data analysis technique used multiple linear regression analysis. SPSS 23 software for windows is used to help analyze the relationship between variables. The results showed that City Image, City Branding, and eWOM had a significant effect on visiting decisions.